2014
DOI: 10.1155/2014/902953
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of Mammalian Sperm Capacitation

Abstract: After ejaculation, the mammalian male gamete must undergo the capacitation process, which is a prerequisite for egg fertilization. The bioenergetics of sperm capacitation is poorly understood despite its fundamental role in sustaining the biochemical and molecular events occurring during gamete activation. Glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) are the two major metabolic pathways producing ATP which is the primary source of energy for spermatozoa. Since recent data suggest that sperma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 79 publications
2
121
1
1
Order By: Relevance
“…These metabolic pathways are localized in the fibrous sheath and midpiece of spermatozoa's flagellum, respectively [54]. AMPactivated protein kinase has emerged as one of the regulators of the mitochondrial membrane potential, DJm, in spermatozoa from boars [43] and mice [45].…”
Section: Role Of Ampk Pathway In the Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…These metabolic pathways are localized in the fibrous sheath and midpiece of spermatozoa's flagellum, respectively [54]. AMPactivated protein kinase has emerged as one of the regulators of the mitochondrial membrane potential, DJm, in spermatozoa from boars [43] and mice [45].…”
Section: Role Of Ampk Pathway In the Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…The present results indicate that spermatozoa require glucose to support optimal motility, even when media is supplied with lactate and pyruvate that support mitochondrial respiration. In fact, mammalian sperm require metabolic energy for a variety of functions (Williams & Ford 2001, Ferramosca & Zara 2014, and it is known that human spermatozoa obtain a significant proportion of their energy from glycolysis (Williams & Ford 2001). Nevertheless, the origin of ATP for sperm motility is still being intensely discussed (Ford & Harrison 1981, Williams & Ford 2001, Ruiz-Pesini et al 2007, Bucci et al 2011, Piomboni et al 2012.…”
Section: Effects Of Substrate Availability On Spermatozoa Functionalitymentioning
confidence: 99%
“…Moreover, it has been found that oxidative stress negatively affects human sperm mitochondrial respiration 5 and that defects in energy metabolism may play a pivotal role in sperm dysfunctions. 20,21 The aim of this study was to investigate the role of oxidative stress (in blood and The high levels of ROS observed in blood and seminal fluid of varicocele patients might damage the inner mitochondrial membrane in which the respiratory complexes are deeply embedded. When we analyzed the mitochondrial respiratory efficiency, we found that sperm mitochondria of varicocele patients showed a lower RCR value, suggesting a lower coupling between respiration and ATP synthesis.…”
Section: Patient Characteristicsmentioning
confidence: 99%